Evaluation of the accessible urban public green space at the community-scale with the consideration of temporal accessibility and quality - Li, Xin; Huang, Ying; Ma, Xiaodong (Ecological indicators, 2021)
•Urban public green space (PGS) is a key regulator for urban human well-being.•PGS should be evaluated with consideration of accessibility and quality.•Transportation modes have a spatial “flattening effect” on accessible PGS.•Spatial imbalance of PGS quality can exacerbate PGS inequity.•PGS supply strategies including quantity, accessibility and quality were proposed. Urban public green space (PGS) provides a wealth of ecological and social benefits, and is the key for sustainable urban development and human well-being satisfaction. A comprehensive evaluation is an important basis for PGS refined governance and planning. However, few studies have comprehensively explored the fine dimension of PGS quality, accessibility, and population, for the evaluation of accessible PGS and its spatial equity. Therefore, we evaluated the accessible PUS at the community-scale with the consideration of temporal accessibility and PUS quality. We first evaluated the accessible PGS of communities using the two-step floating catchment area (2SFCA) approach based on road network. Secondly, Gini coefficient was employed to examine the spatial equity of community-scale PGS. Finally, we proposed relevant strategies for improving PGS provision. The main findings of this study were: transportation modes did not change the average PGS level but had a spatial “flattening effect” on the accessible PGS. Transportation modes affected PGS equity as they changed the PGS accessibility, and the equity of accessible PGS progressively increases with walking, riding E-bike, and driving. The spatial imbalance of PGS quality exacerbated PGS inequity, not only existing quantity unfair, but also quality unfair. Comprehensive PGS supply improvement strategies were proposed in terms of quantity increase, accessibility improvement, and quality construction. This study is conducive to the implementation of human-scale green space planning, providing a basis for the refined urban management.